THE MAIN IMAGING ISSUES IN THE REALM OF MMS - Silva, João Fernando Custodio da (Revista Brasileira de Cartografia, 2013)
Mobile mapping is a method of acquisition of geo-referenced images that uses a moving platform in which sensors and other devices are set on board. Although the mobile mapping systems (MMS) were built to map roads they were extended to streets, railroads, waterways, environmental areas, and recently entered the buildings, concerning the land-based domain. More recently, MMS concepts were successfully implemented in unmanned aerial vehicles to fly safely. Mobile mapping technology requires measuring, processing and analysis of distinct data types: time, phase, range, force, angular rate, and distance, that provide position, velocity, and attitude (PVA) of one or more image sensors (cameras and LIDAR), which lead to geo-referenced images. The article brings a brief description, evolution, and technologic advances of the method and it also shows the main application branches. The mobile devices, the growing image sensor resolution, the low cost inertial sensors, and the computer performance of the 64-bit processors indicate that this methodology has potential for new applications. These new possibilities demand portability, mobility, and accessibility to sites where PVA have to be estimated by non satellite navigation methods. Image sensors, namely digital cameras and lidar devices, effectively materialize the process of visualization, measurement, recognition, and mapping 3D objects.